2020
DOI: 10.1016/j.mam.2020.100873
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency and supplementation in heart failure and chronic kidney disease

Abstract: Iron is a key element for normal cellular function and plays a role in many cellular processes including mitochondrial respiration. The role of iron deficiency (ID) in heart failure (HF) has been a subject of debate amid increasing advocacy for intravenous (IV) supplementation. Both the definition and the approach to treatment of ID in HF have been adapted from the experience in patients with chronic kidney disease (CKD). In this review, we highlight the differences in regulatory mechanisms as well as pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…A meta-analysis of patients with IBD and IDA demonstrated a higher efficacy of intravenous iron administration in increasing hemoglobin levels compared to oral iron supplementation with consistently fewer gastrointestinal adverse events [250]. In CHF patients with absolute or functional ID parenteral iron supplementation was shown to improve cardiac performance and QoL even independent of concomitant anemia [251][252][253], however, concerns became evident regarding iron accumulation in the myocardium and endothelia and in regard to the need of outcome data [254]. Moreover, several clinical trials investigating iron treatment in anemic cancer patients demonstrated that intravenous (but not oral) iron administration increases hematopoietic response and decreases rate of blood transfusions with a concomitant increase of QoL [255].…”
Section: Iron Replacemant Therapymentioning
confidence: 99%
“…A meta-analysis of patients with IBD and IDA demonstrated a higher efficacy of intravenous iron administration in increasing hemoglobin levels compared to oral iron supplementation with consistently fewer gastrointestinal adverse events [250]. In CHF patients with absolute or functional ID parenteral iron supplementation was shown to improve cardiac performance and QoL even independent of concomitant anemia [251][252][253], however, concerns became evident regarding iron accumulation in the myocardium and endothelia and in regard to the need of outcome data [254]. Moreover, several clinical trials investigating iron treatment in anemic cancer patients demonstrated that intravenous (but not oral) iron administration increases hematopoietic response and decreases rate of blood transfusions with a concomitant increase of QoL [255].…”
Section: Iron Replacemant Therapymentioning
confidence: 99%
“…A number of clinical trials have been conducted to evaluate i.v. iron supplementation in HF patients (110)(111)(112). A published meta-analysis of ten clinical trials on iron supplementation in HF patients revealed that iron administration was associated with improved cardiac function and quality of life and lower risk for hospitalization, although the all-cause mortality rate remained unchanged (113).…”
Section: Heart Failurementioning
confidence: 99%
“…Limitations of the study include its retrospective nature, the small sample size, and the lack of a formal comparison between the incidence of iron deficiency in patients with AF against those without. Multivariate analysis was not performed, and there was a high prevalence of confounding comorbidities such as congestive cardiac failure (35.3%) and chronic kidney disease (33.8%), both of which have an established effect on iron metabolism [ 14 ]. Moreover, the incidence of iron deficiency in our study may be artificially high because of selection bias.…”
Section: Discussionmentioning
confidence: 99%